A Descriptive Study of the Students' Problems in English Reading Comprehension of X grade at SMAS AMKUR Sungai Pinyuh in the Academic year 2021/2022 - Aditya, Denuk Ayu; Antonia, Tia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
This study investigates the problem of student English reading in the Senior High School of SMAS AMKUR Sungai Pinyuh in terms of types of material, reading tasks, and cognitive level of reading tasks. The participant of this study consists of 23 students of grade X Social Studies. The researchers used descriptive qualitative research to develop the material in teaching reading, especially for English subjects. Not only for the texts, vocabulary, and the information but also to build students